ANALISIS DETERMINAN YANG MEMPENGARUHI KUALITAS LABA STUDI PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (PERIODE 2012 – 2016) - Heni Kusumawati; Shita Lusi Wardhani (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2018)
This study aims to obtain empirical evidence on the relationship of factors that affect the Company's Profit Quality as expressed by Earnings Response Coefficient (ERC). Exogenous variables in this study include Institutional Ownership, Debt Structure, Debt Structure on Institutional Attribution, Growing Opportunities, Company Size of Systematic Risk and Consistency of Profit. The research sample is manufacturing companies listing on Indonesia Stock Exchange with research period year 2011-2015. The number of research samples is 615 samples with the number of manufacturing companies that meet the sample requirements of 123 companies consisting of 18 industry groups. The method of analysis by using multivariate regression, obtained the findings indicate that the size of the company (size) significantly influence the direction of positive relationship to the Quality of Earnings presented in the financial statements. While the variable of Institutional Ownership, Debt Structure, Debt Structure on Institutional Attribution, Growing Opportunity, Systematic Risk and Consistency Profit is not proven to have a significant effect on Company's Profit Quality.